Linking livelihood and ecosystem change in two dryland sites in Southern Africa over a period of 30 years - Masunungure, Current (Rhodes University, Faculty of Science, Department of Environmental Science, 2017)
The ongoing and rapid change (from global to local level) in climate, populations, governments, cultures, environment, land use and economies are critical issues, especially for poor rural communities found in the dryland parts of southern Africa. The manifestations of change can combine to increase rural livelihood vulnerability, through the erosion of assets and insecurity, but can at the same time create new opportunities. Studies that consider the complex nature of change across scales and how it affects changes in livelihoods, ecosystems and responses at local level, are increasingly needed. This study, carried out in two purposefully selected study sites in the communal drylands of south-eastern Zimbabwe (Marwendo village) and Limpopo province in South Africa (Tshivhulani village), examined the complex nature of change across scales by assessing the way in which change at the global scale results in localised trends, shocks and stressors, and its impacts on livelihoods and ecosystems and responses over the past 30 years. The study applies social-ecological system thinking in understanding human-environment change. Particular emphasis was put on the role of social protection and natural resources in responding to change, shocks and stressors. The study employed a mixed method approach to gather data which included a household survey, life history interviews, transect walks, focus group discussions as well as secondary sources of information. The results of the study illustrate that shocks and stressors are common in both villages and are likely to increase in severity and frequency with ongoing and rapid human-environmental change, especially climate change. The local responses to change, shocks and stressors are primarily reactive and mainly intensify exploitation of existing natural resources and social protection as safety-nets. In Marwendo village, the villagers relied more on the use and sale of natural resource products readily available to them, whereas in Tshivhulani village they mainly tend to rely on social grants. Thus, in the future, households' vulnerability might increase, and may be worse in Marwendo village, since important components of current livelihoods remain natural resource-based and climate sensitive. In Tshivhulani village, livelihoods characterised by high dependence on social grants can have severe consequences for households as children get older or elderly members die and grants cease to be available. Social grants therefore only really offer a temporary relief. This coupled with environmentally destructive practices such as brick-moulding in Marwendo village and uncontrolled settlements in Tshivhulani village may reinforce the negative impacts of change and thus undermine sustainable adaptation. The study concludes that multiple lenses for understanding the links between livelihood and ecosystem vulnerability in the context of the ongoing and rapid change are essential, and these provide insights into how different policy options for livelihood improvement and social protection might be appropriate for reducing household and ecosystem vulnerabilities in the future.
Keywords: Marwendo Village (Zimbabwe) -- Social conditions; Tshivhulani Village (South Africa) -- Social conditions; Marwendo Village (Zimbabwe) -- Environmental conditions; Tshivhulani Village (South Africa) -- Environmental conditions; Climatic changes -- South Africa -- Tshivhulani Village; Climatic changes -- Zimbabwe -- Marwendo Village